Without Nuremberg—What? - Henry T. King Jr. (Washington University Global Studies Law Review, 2007)
One of the difficulties in comparing Nuremberg to its modern descendents is that the Nuremberg Trials were conducted under ideal conditions. Germany and Italy had unconditionally surrendered and the defendants were already in the custody of and under the control of the victorious powers, as was the enormous amount of incriminating documentary evidence. The world’s nation states as a whole endorsed the trials, and the daily press coverage made its proceedings transparent to and understandable by the general public, including the Germans. The modern war crimes tribunals have not been conducted under the same ideal circumstances. Major powers on the United Nations (“U.N.”) Security Council have not given their unstinted support, particularly when they deem their self-interests are at stake. Financial short-falls have hampered the gathering of evidence and the apprehension of indicted defendants, both tasks which have been made even more difficult by uncooperative local governments. And sparse media coverage, with the exception of “superstar” defendants like Slobodan Milosevic and Saddam Hussein, has resulted in apathy, misunderstandings, opposition, and proceedings wholly unknown to the victims. Still, these courts have implemented the Nuremberg principles and have even expanded on the crimes over which they have jurisdiction to now include rape, sexual violence, and the forced use of children as soldiers. In spite of the imperfections, they are carrying on the legacy of Nuremberg. Nuremberg was designed to replace the Law of Force with the Force of Law. This was, indeed, a revolutionary concept.
Keywords: Nuremberg War Crime Trials; Nuremberg; Germany; 1945-1949; War crimes; International criminal law; Crimes against humanity; Rule of law; Sovereignty